Risk analysis in bao bun production processes using FMEA and FTA methods: a case study - Gusti, Nastiti Caket; Tosungku, La Ode Ahmad Safar; Gunawan, Suwardi (Operations Excellence: Journal of Applied Industrial Engineering, 2024)
Risks are present in every activity and could cause damage if not properly addressed. This research discusses how to identify risks that occur in the production process of the food industry. The characteristics of the goods, such as flavor, price, appearance, and availability, are met through the production process by transforming raw materials into products. The XX Bakery business experiences several risks at the production stage that reduce the quality of the product which potentially causes financial losses. Failure Mode and Effect Analysis (FMEA) is used to identify and assess the risks and their level of importance. There were 20 risks that occurred in the production process obtained through observation and interviews. The risks were then assessed based on severity, occurrence, and detection through a questionnaire to determine the Risk Priority Number (RPN) value. The Pareto chart shows which risks would result in a significant impact if given treatment. There were top 5 risks in which RPN values resulted in 80% of the total score. The risks are broken mixer with a score of 360, fluctuation of raw material prices with a score of 320, power outages with a score of 240, workers experiencing fatigue with a score of 144, and water supply stopped with a score of 60. The risks were then further analyzed using Fault Tree Analysis (FTA) to find their root causes. The results of the risk management processes serve as a base for consideration in forming proposals for corrective actions that improve risks—the implementation of the proposed improvements is expected to reduce losses that potentially be experienced by the business.